Design, synthesis and biological evaluation of new aryl thiosemicarbazone as antichagasic candidates - Blau, Lorena [UNESP]; Menegon, Renato Farina; Trossini, Gustavo H. G.; Molino, João Vitor Dutra; Vital, Drielli Gomes; Cicarelli, Regina Maria Barretto [UNESP]; Passerini, Gabriela Duó [UNESP]; Bosquesi, Priscila Longhin [UNESP]; Chin, Chung Man [UNESP] (Elsevier, 2013)
The present work reports on the synthesis, biological assaying and docking studies of a series of 12 aryl thiosemicarbazones, which were planned to act over two main enzymes, cruzain and trypanothione reductase. These enzymes are used as targets of trypanocidal activity in Chagas disease control with a minimal mutagenic profile. Three p-nitroaromatic thiosemicarbazones showed high activity against Trypanosoma cruzi in in vitro assays (IC50 < 57 μM), and no mutagenic profile was observed in micronucleous tests. Although the in vitro inhibition test showed that 10-μM doses of eight compounds inhibited cruzain activity, no correlation was found between cruzain inhibition and trypanocidal activity. © 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Chagas disease; Cruzain; Docking; Mutagenicity; Oxidative stress; Thiosemicarbazone; 2 amino 1 (3 nitrophenyl)ethan 1 one thiosemicarbazone; 2 amino 1 (4 nitro) acetophenone thiosemicarbazone hemisuccinate amide; 2 amino 1 (4 nitro)acetophenone thiosemicarbazone; 2 amino 1 phenylethan 1 one thiosemicarbazone; 2 hidroxy 1 (4 nitro) acetophenone thiosemicarbazone hemisuccinate ester; 2 hydroxy 1 (4 nitro)acetophenone thiosemicarbazone; 3 amino 4 nitroacetophenone thiosemicarbazone; 3 nitro 4 aminoacetophenone thiosemicarbazone; 4 aminoacetophenone thiosemicarbazone; acetophenone thiosemicarbazone; aminoacetophenone thiosemicarbazone; antiprotozoal agent; cruzipain; thiosemicarbazone derivative; trypanothione reductase; unclassified drug; antiprotozoal activity; biological activity; bromination; concentration response; drug design; drug mechanism; drug structure; drug synthesis; IC 50; in vitro study; melting point; molecular docking; mutagenic activity; mutagenicity; nonhuman; trypanocidal activity; Trypanosoma cruzi